Voices from the margins: navigating the organizational support experience of adjunct faculty at a multi-campus community college - McNeil, Zachary K. (My University, 2025)
This interpretive phenomenological study explores the organizational support experiences of adjunct faculty at a multi-campus community college. As adjunct faculty increasingly comprise most instructional staff in U.S. community colleges, understanding their lived experiences is essential to improving institutional effectiveness and student outcomes. By examining institutional structures and the social dynamics between adjunct faculty and their colleges, the study investigates how adjunct faculty perceive support and identifies systemic challenges that influence their performance and well-being. Data was collected through three rounds of semi-structured interviews with 11 adjunct faculty members across four campuses. Thematic analysis revealed four central themes: (a) communication, (b) isolation, (c) overwhelmed, and (d) recognition. Participants described fragmented and impersonal communication, limited access to resources, emotional fatigue, and a lack of meaningful inclusion in institutional culture. Despite these challenges, adjunct faculty expressed a strong commitment to teaching and a desire for more equitable support. Findings suggest that adjunct faculty effectiveness is not inherently inferior to full-time faculty but is shaped by disparities in organizational support. Recommendations include: (a) improving communication practices, (b) fostering community, (c) managing workloads, and (d) embedding recognition into institutional policy. The research contributes to the literature on adjunct faculty by centering their voices and offering actionable strategies for enhancing their support experience. The implications extend beyond the study site, offering insights for other colleges seeking to improve adjunct faculty engagement, retention, and student success.
Voices from the margins: the organizational support experience of adjunct faculty at a multi-campus community college
Keywords: Organizational support; Adjunct faculty; College; Qualitative